Pendidikan Pranatan di Keraton Surakarta - Pujianto Pujianto (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Customs and Manners Education at Keraton Surakarta (Surakarta Kingdom). Keraton Kasunanan and Kadipaten Mangkunegaran are genealogically of Kerajaan Mataram (Mataram Kingdom), which enforces customs and manners education for monarchic life. The customs and manners which are currently implemented refer to the ones established by Pakubuwana X and Mangkunegara VII and are reflected in arts, behaviors, language, and art of clothing under the sovereignty of Pakubuwana XII and Mangkunegara IX.